Young Customers’ Expectations in Terms of Implementing PropTech (Property Technology) on the Local Primary Residential Market in Poland - Strączkowski, Łukasz; Górska, Anna; Mazurczak, Anna (Research Papers in Economics and Finance, 2021)
The aim of this study is to assess customers’ expectations in the use of modern technologies in the process of buying and subsequent use of flats on the local primary residential real estate market. The study has been conducted in order to achieve the above-mentioned goal. A survey questionnaire was used as a research tool. The subjects were young people (up to 35 years of age) from the area of Poznań (non-random sample selection, sample size n=220). Based on the research, it can be concluded that there is a large group of customers that are aware of modern technologies and claim that they would be willing to pay more for the technologies they choose. Probably this number could be increased if the buyers were pointed to specific savings from investing in modern solutions. The adopted spatial scope (city of Poznań) results from the specificity of this research area. And although there are no substantive grounds for major generalisations, taking into account the size of the market in Poznań, it can be assumed that in other large Polish cities customer preferences are similar.